2021
DOI: 10.1016/j.celrep.2021.109743
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar spreading depolarization mediates paroxysmal movement disorder

Abstract: Highlights d PRRT2 deficiency sensitizes cerebellar cortex to spreading depolarization (SD) d PRRT2 deficiency facilitates cerebellar SD by increasing Na v channel availability d SD disturbs DCN neuronal firing and mediates dyskinetic episodes d Inhibiting Na v channels prevents cerebellar SD and alleviates dyskinesia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 76 publications
0
30
0
Order By: Relevance
“…With further experimentation, the team was able to find that the inactivation of sodium channels was sufficient to block cerebellar SD. This result may help to explain the effectiveness of carbamazepine in the treatment of PKD [18]. The effectiveness of carbamazepine in treating the symptoms of our PNKD patient may suggest that similar pathophysiology may be implicated between PNKD and PKD, although future research should focus on elucidating the role of SD in the pathologic process of the various PD subtypes.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…With further experimentation, the team was able to find that the inactivation of sodium channels was sufficient to block cerebellar SD. This result may help to explain the effectiveness of carbamazepine in the treatment of PKD [18]. The effectiveness of carbamazepine in treating the symptoms of our PNKD patient may suggest that similar pathophysiology may be implicated between PNKD and PKD, although future research should focus on elucidating the role of SD in the pathologic process of the various PD subtypes.…”
Section: Discussionmentioning
confidence: 67%
“…As expected from the similar phenotype across different PD subtypes, the different genetic mutations all converge into a limited range of pathologic pathways that ultimately leads to neurotransmission disruption, mostly in the cerebellar and striatal circuits [17]. A recent study by Lu et al further elucidates this mechanism by drawing an association between PRRT2 deficiency and increased induction of cerebellar spreading depolarization (SD), demonstrating that SD can cause a depolarization block of Purkinje cells and disturb cerebellar outputs, leading to dyskinetic movements in PKD [18]. The study also confirmed the effect of the PRRT2 mutation on the SNARE complex and the voltage-gated sodium channels.…”
Section: Discussionmentioning
confidence: 99%
“…Spreading depolarization is one of the most important pathophysiological processes of the CNS, with far-reaching implications for neurology, and there, not only for migraine with aura, but also for the most diverse forms of acute injury of the cerebrum and most likely also of the cerebellum, brainstem and spinal cord, and even for paroxysmal movement disorders ( Lu et al, 2021 ). Spreading depolarization is among the most basic pathological processes in the nervous system that appeared in phylogenesis even before the development of a proper blood circulation ( Spong et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of experimental data have contributed to the understanding of PRRT2 function and pathogenesis of paroxysmal disorders associated with loss-of-function mutations in PRRT2 , that has been described as a network stability gene ( 16 , 17 ). We and other groups have found that genetic deletion of the PRRT2 gene in the mouse (PRRT2KO) mimics the human pathology and displays network hyperexcitability particularly in brain areas where PRRT2 is highly expressed, such as the cerebellum and the hippocampus ( 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ). Physiological levels of PRRT2 seem to be necessary to maintain a normal level of network activity, so that an overexpression of PRRT2, occurring in the 16p11.2 duplication, is also associated with neuropsychiatric disorders including epilepsy ( 26 ).…”
mentioning
confidence: 99%